Icariin Promotes Survival, Proliferation, and Differentiation of Neural Stem Cells In Vitro and in a Rat Model of Alzheimer’s Disease - Denglei Ma; Lihong Zhao; Li Zhang; Yali Li; Lan Zhang; Lin Li (Stem Cells International)
Alzheimer’s disease (AD) involves the degeneration of cholinergic neurons in the basal forebrain. Neural stem cell (NSC) transplantation has emerged as a promising therapeutic approach for treating AD. Icariin (ICA) is the main active component in Epimedium, a traditional Chinese herb. The purpose of the present study was to investigate the effects and mechanisms of ICA on the proliferation and differentiation of NSCs in the basal forebrain of a fimbria-fornix transection (FFT) rat model. In the present study, ICA promoted the survival, proliferation, and migration of NSCs in vitro. In FFT rats, ICA promoted the proliferation and differentiation of NSCs into neurons and increased the number of cholinergic neurons in the MS and VDB of the basal forebrain. These results suggest that combination therapy of ICA oral administration and NSC transplantation may provide a new potential and effective approach for AD therapy.